Biological Tools to Deal with Pollution : Selected Advances and Novel Perspectives - Abdelaziz Ghanemi; Besma Boubertakh (International Journal of Public Health Science (IJPHS), 2014)
Pollution  represents  a  problem  common  to economy and  public  health. Indeed, the public health, because of the  divers’  type of pollutions, is facing divers challenges for which urgent solutions are required.The biology provides approaches not only to deal with the pollution, but also to  obtain  economic  benefits. Some living  organisms  have  particular metabolisms  that allow  them  to  assimilate  and  metabolite  the polluting agents  and thus reduce the  impact  they have on both environment  and public health.  On  the other  hand,  the  metabolic  properties  of  specific organisms make  the  polluting  elements raw materials to  synthesize  other elements that are benefits  for  economy  and  non-toxic  for  the  ecology and  the  biohealth. Yet, other options such as the regulations and laws are  required  to improve the efficiency of these approaches.